2022
DOI: 10.3390/cimb44100319
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Inflammatory and Anti-Inflammatory Salivary Cytokines in Breast Cancer: Relationship with Clinicopathological Characteristics of the Tumor

Abstract: The aim of the work was to compare the salivary cytokine profile of breast cancer patients with the clinicopathological characteristics of the tumor. The study included 113 patients with breast cancer (main group, mean age 54.1 years) and 111 patients with breast fibroadenomas (control group, mean age 56.7 years). Before treatment, saliva samples were collected from all patients and the content of cytokines (IL-1β, IL-2, IL-4, IL-6, IL-8, IL-10, IL-18, MCP-1, and TNF-α) was determined. The content of cytokines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Granulocyte‐Macrophage Colony‐Stimulating Factor (GM‐CSF) and CCL‐5 from BC cells have similar abilities to enhance tumor cell infiltration and metastasis [30,47,56] . Interferon‐γ (IFN‐γ), Tumor Necrosis Factor‐α (TNF‐α), and Granzyme B in BC cells have both antitumor activity and tumorigenic effects [51,57,58] . Many other factors must be considered when weighing their benefits and drawbacks on cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Granulocyte‐Macrophage Colony‐Stimulating Factor (GM‐CSF) and CCL‐5 from BC cells have similar abilities to enhance tumor cell infiltration and metastasis [30,47,56] . Interferon‐γ (IFN‐γ), Tumor Necrosis Factor‐α (TNF‐α), and Granzyme B in BC cells have both antitumor activity and tumorigenic effects [51,57,58] . Many other factors must be considered when weighing their benefits and drawbacks on cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…It has been established that inflammatory factors like Interleukin-1β (IL-1β), Interleukin-2 (IL-2), Interleukin-6 (IL-6), and Interleukin-8 (IL-8) can promote tumor growth and the progression of breast cancer, such as cell proliferation, migration, and invasiveness. [42,46,51,52] Chemokine (C-C motif) Ligand 5 (CCL-5), Cancer Antigen 153 (CA153), and Human Epididymis Protein 4 (HE4) are considered promising potential biomarkers for the diagnosis and metastasis prediction of BC. [33,53,54] Heat Shock Protein 70 (HSP70) is basally expressed in cells under normal circumstances.…”
Section: The Effect Of Zno Nrs On Cytokines From the Cell Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrarily, literature demonstrated IL-18 as a pro-oncogenic cytokine (Ref. 75) where its expression in BC led to enhanced invasion, metastasis (Refs 76, 77, 78, 79, 80, 81), migration (Refs 76, 82), proliferation (Ref. 83), angiogenesis (Ref.…”
Section: What Are Inflammasomes?mentioning
confidence: 99%
“…In a study conducted by Bel’skaya LV et al, significant increases in the levels of MCP-1, IL-1β, IL-2, IL-4, and IL-10 were reported in triple-negative breast cancer. Furthermore, a robust association was found between the levels of TNF-α, IL-1β, and IL-6 with HER2 status [ 3 ]. Observational studies have indicated that increased levels of inflammatory cytokines, specifically IL-6, are linked to a greater risk of recurrence and metastasis in early breast cancer patients who are HER2-negative [ 4 ].…”
Section: Introductionmentioning
confidence: 99%